Importance of exercise testing shortly after subcutaneous implantable cardioverter-defibrillator implantation in patients with Brugada syndrome – The first case of associated inappropriate shock in Japan - Kohei Ishibashi, MD, PhD; Takashi Noda, MD, PhD; Tsukasa Kamakura, MD, PhD; Mitsuru Wada, MD; Yuko Inoue, MD, PhD; Hideo Okamura, MD, PhD; Kengo Kusano, MD, PhD (Journal of Arrhythmia, 2017)
We report the case of a 51-year-old patient with Brugada syndrome (BrS) who experienced inappropriate shock due to T-wave oversensing (TWOS) during exercise when the optimal sensing vector was selected based on the automatic analysis by a subcutaneous implantable cardioverter-defibrillator (S-ICD). After selecting another vector during exercise testing, TWOS did not re-occur. Selection of appropriate sensing vector based on analyses under various conditions, including during exercise after S-ICD implantation, should be considered for patients with BrS.